The temple of the wild geese and Bamboo dolls of Echizen - Minakami, Tsutomu (Dalkey Archive Press, 2008)
The Temple of the Wild Geese, a semi-autobiographical account of Mizukami's childhood, tells the tale of Jinen, a Buddhist monk raised by villagers after his mother, a beggar, abandoned him. Sent to live at a temple at the age of ten, his resentment smolders for years until it explodes in a shocking climax." "In Bamboo Dolls of Echizen, no woman is wiling to marry the diminutive Kisuke, a bamboo artisan, until Tamae, a prostitute, comes to pay her respects at the grave of Kisuke's father. In Tamae, Kisuke sees shadows of his own mother, who died when he was young, and the two eventually marry. Since Kisuke seeks only motherly affection from Tamae, the two never become lovers. Instead, Tamae devotes herself to caring for Kisuke as a mother would, and he thrives as a renowned maker of bamboo dolls." (BOOK JACKET)